Dynamic Relationship Between Interhemispheric Functional Connectivity and Corticospinal Tract Changing Pattern After Subcortical Stroke - Liu, Jingchun; Wang, Caihong; Cheng, Jingliang; Miao, Peifang; Li, Zhen (Frontiers in Aging Neuroscience, 2022)
Background and Purpose Increased interhemispheric resting-state functional connectivity (rsFC) between the bilateral primary motor cortex (M1) compensates for corticospinal tract (CST) impairment, which facilitates motor recovery in chronic subcortical stroke. However, there is a lack of data on the evolution patterns and correlations between M1–M1 rsFC and diffusion indices of CSTs with different origins after subcortical stroke and their relations with long-term motor outcomes. Methods A total of 44 patients with subcortical stroke underwent longitudinal structural and functional magnetic resonance imaging (MRI) examinations and clinical assessments at four time points. Diffusion tensor imaging was used to extract fractional anisotropy (FA) values of the affected CSTs with different origins. Resting-state functional MRI was used to calculate the M1–M1 rsFC. Longitudinal patterns of functional and anatomic changes in connections were explored using a linear mixed-effects model. Dynamic relationships between M1–M1 rsFC and FA values of the affected specific CSTs and the impact of these variations on the long-term motor outcomes were analyzed in patients with subcortical stroke. Results Stroke patients showed a significantly decreased FA in the affected specific CSTs and a gradually increasing M1–M1 rsFC from the acute to the chronic stage. The FA of the affected M1 fiber was negatively correlated with the M1–M1 rsFC from the subacute to the chronic stage, FA of the affected supplementary motor area fiber was negatively correlated with the M1–M1 rsFC in the subacute stage, and FA of the affected M1 fiber in the acute stage was correlated with the long-term motor recovery after subcortical stroke. Conclusion Our findings show that the FA of the affected M1 fiber in the acute stage had the most significant correlation with long-term motor recovery and may be used as an imaging biomarker for predicting motor outcomes after stroke. The compensatory role of the M1–M1 rsFC enhancement may start from the subacute stage in stroke patients with CST impairment.